FeNx/FeSx-anchored carbon sheet-carbon nanotube composite electrocatalysts for oxygen reduction - Bhange, Siddheshwar N.; Soni, Roby; Singla, Gourav; Ajithkumar, T. G.; Kurungot, Sreekumar (ACS Applied Nano Materials, 2020)
Even though various Pt-free electrocatalysts for oxygen reduction reaction (ORR) have been introduced, many of them are found to be active only in alkaline conditions. Considering Nafion, phosphoric acid-doped polybenzimidazole (PBI), and so on as the prominent ionomer membranes, used in the commercially available polymer electrolyte membrane fuel cells (PEMFCs), it becomes important that any development on the Pt-free catalysts should ensure the better ORR performance under acidic conditions. The present work effectively tackles this issue, where an ORR-based catalyst could be prepared with simultaneous incorporation of both Fe-N and Fe-S active sites on in situ generated carbon sheets which are spatially separated by the carbon nanotube (CNT) network. This catalyst shows ability to perform under both acidic and basic conditions. This has been achieved by growing a polyethylenedioxythiophene polymer network in the presence of CNT and melamine followed by its pyrolysis under an inert atmosphere. The catalyst formed at 900 degrees C (PMCNT-900) displays 0.94 V onset potential for ORR under acidic electrolyte conditions, which corresponds to 60 mV overpotential compared to its 40 wt % Pt/C counterpart. Interestingly, in single cell demonstration of Nafion-based PEMFC with PMCNT-900 as the cathode catalyst, the system delivered a maximum power density (PD) of 500 and 275 mW/cm(2) at 60 degrees C under H-2-O-2 and H-2-air feed conditions, respectively. On the other hand, in a single cell test in the anion exchange membrane fuel cell (AEMFC) mode, a maximum power density of 65 mW/cm(2) at 50 degrees C could be achieved with the same cathode catalyst, which is a comparable value obtained while employing Pt/C as the cathode. These results, thus, infer to the efficiency of the catalyst to facilitate ORR under the extreme pH conditions, and particularly its performance under acidic condition reveals its prospect as a potential Pt-free electrocatalyst to serve in the Nafion-based systems.
Keywords: carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction; Pt-free ORR

Fly-ash-based geopolymers: leachability and solid-state NMR investigations - Nadol, Athulya; Ajithkumar, T. G.; Singla, Rashmi; Alex, T. C.; Kumar, Sanjay; Bhatt, Himal; Deo, M. N.; Sen, Debasis; Ambashta, R. D.; Bajpai, R. K.; Shivakumar, Y. C.; Manohar, S. (Bulletin of Materials Science, 2026)
This study aims to explore how leaching impacts the microstructure of a selected fly ash-derived geopolymer and evaluate its potential for near-surface disposal of radioactive waste. The uniqueness of this geopolymer formulation is its ability to form an aluminosilicate network that remains resistant to structural changes upon contact with water. The leach index of base elements such as Ca, Al, Na and Si was between 11 and 13, suggesting that the formulation is superior to Portland cement or conventional hydraulic cement. Solid-state NMR reveals that the water-interacted specimen has no contamination of the zeolite phase and all the Na is incorporated into the aluminosilicate geopolymer gel network, which also confirms that the glassy network of the geopolymer is responsible for imparting low leachability of base elements from its structure, and there is no labile sodium available for exchange as in zeolites.
Keywords: aluminosilicate network; Fly ash; Geopolymers; leaching; Solid-state NMR